ANALISIS PENGARUH FINANCIAL STABILITY PRESSURE, FINANCIAL DISTRESS, DAN FINANCIAL TARGET TERHADAP POTENSI FINANCIAL STATEMENT FRAUD PADA PERUSAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Liver Nando Sng, Evin; Afrizal; Wiralestari (Jurnal Ilmiah Ekonomi Bisnis, 2024)
This research aims to determine (1) the influence of financial stability pressure on financial statement fraud in property and real estate companies listed on the Indonesia Stock Exchange for the 2020-2022 period. (2) The effect of financial distress on financial statement fraud in property and real estate companies listed on the Indonesia Stock Exchange for the 2020-2022 period. (3) The influence of financial targets on financial fraud in property and real estate companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling technique in this research used documentaries and literature studies of real estate and property companies listed on the Indonesia Stock Exchange (BEI) during the 2018-2022 research period. The sampling method used in this research is the Purposive Sampling Method. The analysis test tool used is SPSS For Window Version 25. The results of this research show that (1) Financial Stability Pressure simultaneously has a positive effect on Financial Statement Fraud. (2) Financial Distress has a positive effect on Financial Statement Fraud. (3). Financial Target has a positive effect on Financial Statement Fraud.